KAJIAN SIFAT FISIKA TANAH DAS SUMPUR BAGIAN HULU KABUPATEN TANAH DATAR - Yulnafatmawita Yulnafatmawita; Asmar Asmar; Aulia Rahman (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2007)
A research about study of soil physical properties in upper part of Sumpur Watershed in Tanah Datar Regency, West Sumatra was conducted in 2005. The objective of the research was to supply information about soil physical properties in the upper part of Sumpur watershed. These data are important to predict the erosion that can happen in that area and the impact to the surrounding area. Survey method with purposive random sampling was employed to this research for sampling soil in the field. Soil was sampled from each land use randomly. There were four types of land use found in the area, those were forest, mixed wood, annual season crops, and rice field. Based on field observation it was found that there were two classes of soils there, Andisols and Inceptisols. The results of laboratory analyses showed that soil texture in Andisols was silt loam, it was the same for each land use. Soil texture in Inceptisols, however, was finer than that in Andisols, it was clay. Bulk volume and total pores of both Andisol and Inceptisol for each land use were not yet different from those in the forest land use. Then, the value for plant available water, drainage pores, and water retaining pores in each land use for both soils were still comparable to those in forest and use. However, soil organic carbon (OC) content tended to decrease as land use change from forest to mixed wood, annual season crops, and rice field at both soils except for mixed wood land use in Inceptisol. The soil OC in that land use was slightly higer than that in the forest. Key Words: land use, soil OC, soil physical properties